Peningkatan Risiko infeksi Multi Drugs Resitant Tuberculosis (MDR-TB) pada Penderita Human Immunodeficiency Virus (HIV) - Dwiki Wijaya Rahman; Ety Apriliana (Majority, 2020)
HIV infection is the biggest challenge for tuberculosis control efforts. People with HIV will have a greater potential to be infected with tuberculosis as an opportunistic disease or to aggravate existing tuberculosis into active tuberculosis. MDR-TB is tuberculosis that is resistant to at least 2 types of anti-tuberculosis drugs (OAT). HIV sufferers will be more at risk of experiencing MDR-TB coinfection due to several reasons, one of which is HIV infection which can cause OAT malabsorption, such as rifampin and ethambutol, too much treatment causes patient non-compliance with treatment, and the possibility of HIV and MDR-TB sufferers who are in areas of the same prevalence, such as in hospitals and densely populated environments, cause the transmission of MDR-TB is more susceptible to HIV sufferers due to a weakened immune system.